2020
DOI: 10.1177/1938640020971419
|View full text |Cite
|
Sign up to set email alerts
|

Arthrodesis or Open Reduction Internal Fixation for Lisfranc Injuries: A Meta-analysis

Abstract: The purpose of this study is to determine if arthrodesis, compared with open reduction and internal fixation (ORIF), produces favorable American Orthopaedic Foot and Ankle Society (AOFAS) and visual analogue scale (VAS) scores, and to determine if differences in complication, revision surgery, and secondary arthrodesis rates exist for patients with Lisfranc fracture/dislocation injuries. Searches were performed in PubMed using the keywords “Lisfranc fracture,” “metatarsal fracture,” “ORIF,” “open reduction int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Clinicians and researchers have evaluated the outcomes of different surgical techniques for Lisfranc injuries; each of these techniques has shown several pros and cons with no definite consensus on superiority for one among others [ 17 ]. A recent meta-analysis by Levy et al suggests that arthrodesis could be a better surgical intervention for patients with Lisfranc injuries, resulting in improved outcomes measured by the American Orthopaedic Foot and Ankle Society ankle-hindfoot score and lower complication rates compared to ORIF [ 18 ]. Furthermore, Buda et al showed that Lisfranc patients treated with ORIF had significantly higher reoperation rates in comparison with those who received PA [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians and researchers have evaluated the outcomes of different surgical techniques for Lisfranc injuries; each of these techniques has shown several pros and cons with no definite consensus on superiority for one among others [ 17 ]. A recent meta-analysis by Levy et al suggests that arthrodesis could be a better surgical intervention for patients with Lisfranc injuries, resulting in improved outcomes measured by the American Orthopaedic Foot and Ankle Society ankle-hindfoot score and lower complication rates compared to ORIF [ 18 ]. Furthermore, Buda et al showed that Lisfranc patients treated with ORIF had significantly higher reoperation rates in comparison with those who received PA [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…14,22,26 Recent studies have demonstrated that individuals treated with primary arthrodesis have a much lower rate of additional surgery and comparable or superior patient-reported outcome scores than those treated with ORIF. 1,12,24 Thus, primary arthrodesis is considered an effective surgical management strategy for Lisfranc injuries.…”
Section: Introductionmentioning
confidence: 99%